A novel clinical score (InterTAK Diagnostic Score) to differentiate takotsubo syndrome from acute coronary syndrome: results from the International Takotsubo Registry - Templin-Ghadri, Jelena-Rima; Franke, Jennifer; Katus, Hugo (European journal of heart failure, 2017)
Aims Clinical presentation of takotsubo syndrome (TTS) mimics acute coronary syndrome (ACS) and does not allow differentiation. We aimed to develop a clinical score to estimate the probability of TTS and to distinguish TTS from ACS in the acute stage. Methods and results Patients with TTS were recruited from the International Takotsubo Registry ( www.takotsubo-registry.com) and ACS patients from the leading hospital in Zurich. A multiple logistic regression for the presence of TTS was performed in a derivation cohort (TTS, n = 218; ACS, n = 436). The best model was selected and formed a score (InterTAK Diagnostic Score) with seven variables, and each was assigned a score value: female sex 25, emotional trigger 24, physical trigger 13, absence of ST-segment depression (except in lead aVR) 12, psychiatric disorders 11, neurologic disorders 9, and QTc prolongation 6 points. The area under the curve (AUC) for the resulting score was 0.971 [95% confidence interval (CI) 0.96-0.98] and using a cut-off value of 40 score points, sensitivity was 89% and specificity 91%. When patients with a score of ≥50 were diagnosed as TTS, nearly 95% of TTS patients were correctly diagnosed. When patients with a score ≤31 were diagnosed as ACS, ∼95% of ACS patients were diagnosed correctly. The score was subsequently validated in an independent validation cohort (TTS, n = 173; ACS, n = 226), resulting in a score AUC of 0.901 (95% CI 0.87-0.93). Conclusion The InterTAK Diagnostic Score estimates the probability of the presence of TTS and is able to distinguish TTS from ACS with a high sensitivity and specificity. Trial registration: NCT0194762